Endocytosis is required for E-cadherin redistribution at mature adherens junctions - de Beco, Simon (National Academy of Sciences, 2009)
E-cadherin plays a key role at adherens junctions between epithelial cells, but the mechanisms controlling its assembly, maintenance, and dissociation from junctions remain poorly understood. In particular, it is not known to what extent the number of E-cadherins engaged at junctions is regulated by endocytosis, or by dissociation of adhesive bonds and redistribution within the membrane from a pool of diffusive cadherins. To determine whether cadherin levels at mature junctions are regulated by endocytosis or dissociation and membrane diffusion, the dynamics of E-cadherin were quantitatively analyzed by a new approach combining 2-photon fluorescence recovery after photobleaching (FRAP) and fast 3D wide-field fluorescence microscopy. Image analysis of fluorescence recovery indicates that most E-cadherin did not diffuse in the membrane along mature junctions, but followed a first order turn-over process that was rate-limited by endocytosis. In confluent cultures of MCF7 or MDCK cells, stably expressed EGFP-E-cadherin was rapidly recycled with spatially uniform kinetics (50 s in MCF7 and 4 min in MDCK). In addition, when endocytosis was pharmacologically blocked by dynasore or MiTMAB, no fluorescence recovery was observed, suggesting that no endocytosis-independent membrane redistribution was occurring. Our data show that membrane redistribution of E-cadherin molecules engaged in mature junctions requires endocytosis and subsequent exocytosis, and lead to the notion that E-cadherins engaged at junctions do not directly revert to free membrane diffusion. Our results point to the possibility that a direct mechanical coupling between endocytosis efficiency and cadherin-mediated forces at junctions could help to regulate intercellular adhesion and locally stabilize epithelia.